The effects of phytosterol in low fat milk on serum lipid levels among mild-moderately hypercholesterolemic subjects (Medical Journal of Indonesia, 2008)
One of the most important risk factors for CHD is dyslipidemia, among others hypercholesterolemia or high LDL-cholesterol. Plant-sterols or phytosterols (PS) are among dietary factors known to lower blood cholesterol as part of therapeutic life-style changes diet. This study was aimed to evaluate the effect of PS properly solubilized in a-partly vegetable oil-filled low fat milk, on serum lipid levels in mild-moderate hypercholesterolemic subjects. Randomized, two-arm parallel control group trial was conducted at Department of Nutrition-University of Indonesia in Jakarta from June to November 2006. Each subject was randomly assigned to receive dietary life-style changes counseling plus 1.2 g phytosterol/day in low-fat milk (PS-group) or control group receiving the counseling alone for six weeks period. There were no significant changes of serum total and LDL-cholesterol of control group after a six week of dietary counseling (respectively 218.3 ± 18.6 mg/dL to 219.6 ± 24.3 mg/dL and 164.7±21.8 mg/dL to 160.0±26.4 mg/dL). There were a significant decreases of serum total and LDL-cholesterol (respectively p=0.01 and p=0.004) among subjects receiving PS after a six weeks observation period (respectively 233.5±24.6 mg/dL to 211.2±30.3 mg/dL and 176.9±24.7 mg/dL to 154.5±24.3 mg/dL). There was a significant difference in the LDL-lowering effects (p=0.024) among the PS-group after a six weeks (22.4±27.9 mg/dL) as compared to the control group (4.7±17.2 mg/dL). No significant changes were found on serum HDL-cholesterol and triglyceride levels in both groups. Although there was no significant difference found in daily nutrients intake between the-2 groups, however, significant reductions in body weight, body mass index and waist circumference were found only in the PS group (p=0.000; 0.000; 0.003, respectively). It is concluded that the lowering of total and LDL-cholesterol in those receiving life-style changes counseling plus 1.2 g PS daily for six weeks was significantly higher as compared to those of receiving counseling alone. (Med J Indones 2008; 17: 5-12) Keywords: TLC Diet, LDL-cholesterol, HDL-cholesterol, triglyceride, phytosterol, body mass index, waist-circumference